2012
DOI: 10.1007/s00540-012-1393-7
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and postoperative early complications in open heart surgery

Abstract: We found that obesity does not increase short-term mortality for open heart surgery; however, it increases the risk of postoperative pulmonary and gastrointestinal complications and discharge with morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
0
14
0
7
Order By: Relevance
“…In recent study, Ranucci [35] and Khairudin [36] found that obese patients are at higher risk for postoperative hypoxia and prolonged ICU stay. In contrast to the published literature, Alam et al [27] and Demir et al [37] reported comparable ICU stay and hospital stay times in obese and non obese patients after CABG. There are disparate results on the association between the obesity and postoperative renal insufficiency.…”
Section: Discussionmentioning
confidence: 71%
“…In recent study, Ranucci [35] and Khairudin [36] found that obese patients are at higher risk for postoperative hypoxia and prolonged ICU stay. In contrast to the published literature, Alam et al [27] and Demir et al [37] reported comparable ICU stay and hospital stay times in obese and non obese patients after CABG. There are disparate results on the association between the obesity and postoperative renal insufficiency.…”
Section: Discussionmentioning
confidence: 71%
“…Demir A et al [23] mentioned that obesity does not increase short term mortality for open heart surgery, however, it increases the risk of postoperative pulmonary complications and discharge with morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association of obesity and PPC is well known [17][18][19] , some studies failed to show the direct correlation between obesity and PPC [20][21][22] . Recent studies have shown that BMI above 35 is linearly associated with increasing PPC; but such correlation is not evident in patients with BMI less than 35 [23,24] . There is 30% chances of developing PPC after abdominal surgery in patients with BMI of 40 and above [25] .…”
Section: Obesitymentioning
confidence: 93%